Lipid-coated hybrid nanoparticles for enhanced bacterial biofilm penetration and antibiofilm efficacy - Lee, Hiang Wee (2023)
Up to 80% of all infections are biofilm-mediated and they are often challenging to treat as the underlying bacterial cells can become 100- to 1000-fold more tolerant toward antibiotics. Antibiotic-loaded nanoparticles have gained traction as a potential drug delivery system to treat biofilm infections. In particular, lipid-coated hybrid nanoparticles (LCHNPs) were investigated on their capability to deliver antibiotics into biofilms. In this study, LCHNPs composed of a poly(lactic-co-glycolic acid) (PLGA) core and dioleoyl-3-trimethylammonium propane (DOTAP) lipid shell were developed and loaded with vancomycin (Van). In vitro antibacterial and antibiofilm tests were performed to evaluate the antimicrobial efficacy of the LCHNPs. LCHNPs were successfully fabricated with high vancomycin encapsulation and loading efficiencies, and exhibited enhanced antibacterial effects against planktonic Staphylococcus aureus USA300 when compared against Free-Van and Van-PLGANPs. When used to treat USA300 biofilms, Van-LCHNPs eradicated up to 99.99% of the underlying biofilm cells, an effect which was not observed for Free-Van and Van-PLGANPs. Finally, we showed that by possessing a robust DOTAP shell, LCHNPs were able to penetrate deeply into the biofilms.